The effectiveness of mHealth interventions for maternal, newborn and child health in low-and middle-income countries: Protocol for a systematic review and meta-analysis - Ulugbek B. Nurmatov; Siew H. Lee; Bright I. Nwaru; Mome Mukherjee; Liz Grant; Claudia Pagliari (Edinburgh University Global Health Society, 2014)
Rates of maternal, newborn and child (MNCH) mortality and morbidity are vastly greater in low- than in high-income countries and represent a major source of global health inequity. A host of systemic, economic, geopolitical and sociocultural factors have been implicated. Mobile information and communication technologies hold potential to ameliorate several of these challenges by supporting coordinated and evidence-based care, facilitating community based health services and enabling citizens to access health information and support. mHealth has attracted considerable attention as a means of supporting maternal, newborn and child health in developing countries and research to assess the impacts of mHealth interventions is increasing. While a number of expert reviews have attempted to summarise this literature, there remains a need for a fully systematic review employing gold standard methods of evidence capture, critical appraisal and meta-analysis, in order to comprehensively map, quality assess and synthesise this body of knowledge.